Analisis Faktor yang Berhubungan dengan Kepuasan Kerja Perawat pada Masa Transisi COVID-19 - Neng Salmah Fauzi Nuraeni; Tri Kurniati; Giri Widakdo; Bram Burmanajaya (Journal of Telenursing (JOTING), 2023)
This study aims to identify an analysis of factors related to nurses' job satisfaction during the COVID-19 transition period. This research method uses a cross-sectional design because the measurements of the independent and dependent variables are measured simultaneously at one time. The results of the research towards the final stage of this modeling, the results obtained based on the table above can be concluded that the value of R Square (R2) = 0.311, which means that the coaching and work motivation variables influence nurses' job satisfaction by 31.1% with the strength of the influence of a strong correlation with a significant p-value = 0,000. From the results of this equation, the regression obtained is nurse job satisfaction = 77.466 - 0.956 (coaching) - 0.942 (motivation)+0.026 (coaching and motivation). The conclusion is that coaching is the most dominant factor related to job satisfaction. Keywords: Coaching, Job Satisfaction, Motivation, COVID-19 Transition Period